(untitled) (Journal of Nuclear Technology in Applied Science, 2020)
Coasts and sea fronts are the most desired destinations on Earth. There are two ways to deal with sea fronts: 1. To remain the property of the government and let them to private companies/developers who create services and make them accessible to the public in exchange for a certain fee. 2. To sell them to private developers who make them private and thus get used by a limited number of people who either own a property in the development and their guests or are hiring in it. The city of Alexandria represents alternative number one; the coast is visible and accessible to the public. From Alexandria city till Mersa Matruh city, alternative two was adopted; the sea is private belonging to private resorts. The public is not able to access the sea only to see it from afar. Far and above, land use can hardly be changed in the future, even if the need for energy projects increase. The objectives of this paper are to save what is remaining from the North coast (Mediterranean Sea) and the East coast (Red Sea) before being transformed into private gated communities. So that, seas remain accessible to all and sites for the construction of nuclear power plants and other renewable energy projects remain a future possibility for future generations.